Cheiloscopy–An Efficient Method for Gender Dimorphism (Medico Legal Update, 2020)
Lip print is an anatomical character of the human lips. In forensic identification, lip print patterns can leadus to important information and helps in person’s identification. The grooves present on human lips (Sulcilabiorum) are unique to each person and can be used to determine identity. Fingerprints, post-mortem reportsand of late, DNA fingerprinting, have been successful in person identification in the field of forensic science.Just as in these method, lip prints can be instrumental in identifying a person positively and can be used toverify the presence or absence of a person at the scene of crime . Cheiloscopic techniques have an equalvalue in relation to other types of forensic evidences for personal identificationMaterial & method:- Thestudy was conducted on 100 students of age group 18-25 yrs. Lip stick was applied on each individual andthe lip-print was obtained on a paper. The lip impression patterns were studied, classified and recordedusing magnifying lens with light.Result:- Lip patterns are unique for the individual and no two patterns areidentical to each other . In study population,Type III pattern was most common in male while In femalespredominant pattern was type I. Thus in medico legal case, due to clear differentiation in sexes it is easy toidentify person and gender. Conclusion:- Cheiloscopy can be reliable method for personal identification andgender dimorphism.